2016
DOI: 10.1038/ctg.2016.3
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of Alpha-Hemolysin by Escherichia coli Disrupts Tight Junctions in Ulcerative Colitis Patients

Abstract: Objectives:The potential of Escherichia coli (E. coli) isolated from inflammatory bowel disease (IBD) patients to damage the integrity of the intestinal epithelium was investigated.Methods:E. coli strains isolated from patients with ulcerative colitis (UC) and healthy controls were tested for virulence capacity by molecular techniques and cytotoxic assays and transepithelial electric resistance (TER). E. coli isolate p19A was selected, and deletion mutants were created for alpha-hemolysin (α-hemolysin) (hly) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 39 publications
0
58
1
Order By: Relevance
“…The potential causal role of IBD-associated E. coli in the pathophysiology of IBD has been linked to the ability to adhere to and invade epithelial cells and multiply within macrophages, such as that seen with the prototypical AIEC strain, LF82. Our studies have shown that UC-associated E. coli (p19A) from the B2 phylogenetic group (ExPEC), harboring two alpha-hemolysin genes, induces cell death in dendritic cells, stimulates the release of the cytokines TNF-␣, IL-6, and IL-23 (99), and causes rapid loss of the TJ integrity in differentiated Caco2-cell monolayers (38). The difference between p19A and strain LF82 is that LF82 does not disturb the epithelial TJ, obviously indicating that these two IBD-associated strains, both from the B2 phylogenetic group, differ in their pathogenic mechanisms.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The potential causal role of IBD-associated E. coli in the pathophysiology of IBD has been linked to the ability to adhere to and invade epithelial cells and multiply within macrophages, such as that seen with the prototypical AIEC strain, LF82. Our studies have shown that UC-associated E. coli (p19A) from the B2 phylogenetic group (ExPEC), harboring two alpha-hemolysin genes, induces cell death in dendritic cells, stimulates the release of the cytokines TNF-␣, IL-6, and IL-23 (99), and causes rapid loss of the TJ integrity in differentiated Caco2-cell monolayers (38). The difference between p19A and strain LF82 is that LF82 does not disturb the epithelial TJ, obviously indicating that these two IBD-associated strains, both from the B2 phylogenetic group, differ in their pathogenic mechanisms.…”
Section: Discussionmentioning
confidence: 94%
“…(34), Listeria monocytogenes (35), Aeromonas hydrophila (36), Proteus spp. (37), E. coli (38,39), and some viruses (40) have all been linked to IBD and are suspected to play a causal role in disease relapses. On looking at these possible IBD pathogenesis links, it is currently unresolved whether the major part is played by specific microorganisms or by the reduced diversity of the microbiota as such.…”
Section: Inflammatory Bowel Disease and The Gut Microbiotamentioning
confidence: 99%
See 1 more Smart Citation
“…Ulcerative colitis (UC) is thought to be caused by some strains of E. coli (340). In cell culture models it has been showed that UC-associated E. coli producing α-hemolysin can cause rapid loss of TJ integrity (341). The human intestinal epithelium is formed by a single layer of epithelial cells that separates the intestinal lumen from the underlying lamina propria and the space between these cells is sealed by TJ, which regulate the permeability of the intestinal barrier (342).…”
Section: Microbiome Effects On Intestinal Barrier Function and Inflammentioning
confidence: 99%
“…Indeed, for example, progression and flares of Inflammatory Bowel Diseases (IBD) may result also from the presence of microbes and microbe‐derived substances in the gut, even after the inciting agents responsible for the initiation of inflammation are controlled (Li et al, ; Wu & Shen, ). Recently, it has been reported that the secretion of alpha‐hemolysin by Escherichia coli disrupts tight junctions in ulcerative colitis patients (Mirsepasi‐Lauridsen et al, ). Meta‐analysis of broad spectrum antibiotic therapy in patients with IBD suggested a short treatment with antibiotics active against hemolysin‐producing E. coli to induce remission in active disease.…”
Section: Introductionmentioning
confidence: 99%